2015
DOI: 10.3389/fmicb.2015.00577
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of antibacterial action of the alcoholic extracts of Hemidesmus indicus (L.) R. Br. ex Schult, Leucas aspera (Wild.), Plumbago zeylanica L., and Tridax procumbens (L.) R. Br. ex Schult

Abstract: Herbal products derived from Hemidesmus indicus (L.) R. Br. ex Schult, Leucas aspera (Wild.), Plumbago zeylanica L., and Tridax procumbens (L.) R. Br. ex Schult. are widely used in traditional medicine. Though the extracts of these plants were found to be antimicrobial in nature and have the potential to be used in clinics, the mechanism of action of is not reported. The ethanolic extracts of Hemidesmus indicus (L.) R. Br. ex Schult, Hemidesmus indicus ethanolic extract (HIEE), Leucas aspera (Wild.), Leucas as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 30 publications
0
47
0
1
Order By: Relevance
“…The crude extracts of plants tend to contain a mixture of molecules that vary in chemical structure and composition, which in turn may influence the biological actions [19]. In literature, the antimicrobial activities of crude extracts of some Pereskia species are reported only for crude extracts of some Pereskia species.…”
Section: Discussionmentioning
confidence: 99%
“…The crude extracts of plants tend to contain a mixture of molecules that vary in chemical structure and composition, which in turn may influence the biological actions [19]. In literature, the antimicrobial activities of crude extracts of some Pereskia species are reported only for crude extracts of some Pereskia species.…”
Section: Discussionmentioning
confidence: 99%
“…A forerunner of the molecular biology approach was the examination of bacteria treated with test agent for changes to their morphology and ultrastructure [24]. This strategy remains extremely popular among researchers investigating antibacterial mechanism of action, both as an early exploratory step [26][27][28][29][30] and for confirmation of a suspected mechanism [31][32][33]. Requiring only access to an electron microscopy suite, it is an approach that is open to researchers in even relatively low resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…SEM images clearly showed rag extract-induced blebbing of bacterial cells, along with aggregation, and change in shape, possibly due to membrane permeabilization. Previous studies have shown that bacterial cells that are normally impermeable to FITC, a fluorescent dye, become FITC-permeant 34 after exposure to alcoholic extracts of various plant extracts mainly due to membrane permeabilization, destabilization, and disruption of membrane potential, resulting in cell blebbing and leakage of cellular contents 27 . In agreement with previous studies on other plant extracts 35 , our results also indicate that JFRE causes changes in bacterial cell morphology that eventually leads to cell death.…”
Section: Discussionmentioning
confidence: 99%